Possibilities of Using of Alkali-activated Mortars in Aggressive Environment. (2016) - Válek, Jaroslav; Jarolím, Tomáš; Labaj, Martin
Abstract: In the article the incipient experimental works about using of alkali-activated mortars in an aggressive environment are introduced. Several types of mortars with different composition were prepared and examined. Observed properties of alkali-activated mortars were: resistance of cement concrete's surface to water and defrosting chemicals, resistance against crack formation and development, adhesion to the concrete base and frost resistance. The purpose of this experiment was to propose a mixture of alkali-activated material that would be suitable for application in the form of a screed for concrete and other materials. The pilot tests were performed with several mixtures with different combinations of initial materials. They were also tested in different mixing ratios, depending on the rheological properties of the respective individual mixtures.